Pengaruh Penambahan Bubuk Jahe Emprit (Zingiber officinale var. Amarum) Terhadap Karakteristik Teh Herbal Celup Kulit Jeruk Manis (Citrus sinensis L.) - Vida Indriani P., Ni Putu; Timur Ina, Putu; Wisaniyasa, Ni Wayan (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 2 (2021): Jurnal ITEPADO - 10.24843/itepa.2021.v10.i02.p04, 2021)
This study aimed to determine the effect of emprit ginger powder ( Zingiber officinale var . Amarum)  on the characteristic of sweet orange peel herbal tea ( Citrus sinensis L.) as well as the appropriateness of emprit ginger powder for the best characteristic. This study was designed using an experimental method which is Completely Randomized Design with the treatment of adding emprit ginger powder (0%, 5%, 10%, 15%, 20%) that was repeated  3 times  to obtain 15 experimental units. Observed variabels were water content, extract water content, vitamin C, total phenolic, total flavonoid, antioxidant activity, scoring test, and hedonic test. The obtained data were analyzed by using the analysis of variance. If it had a significant effect, it was continued to be tested by using the Duncan Multiple Range Test. The results showed that the addition of  emprit ginger powder had a very significant effect on the water content, vitamin C, total phenolic, total flavonoid, antioxidant activity, aroma (scoring and hedonic test), taste (scoring and hedonic test), and overall acceptance, while extract levels in the water had a significant effect and color (hedonic test) had a non significant effect. Furthermore, it showed that the addition of 20% emprit ginger powder extract was the best treatment with the characteristic as follows: 8.13% w / w water content, 26.93% w / d extract water content, vitamin C 25.56 mg / g tea powder, total phenol 17.86 mg GAE / g tea powder, total flavonoids 1.17 mg QE / g tea powder, and antioxidant activity 56.89%. The characteristics of the tea brewing water involves the distinctive aroma of ginger emprit which is very liked, the color is liked, the taste is not bitter and liked, and overall acceptance is liked.